Changes in methylation within the STK32B promoter are associated with an increased risk for generalized anxiety disorder in adolescents. (July 2018) - Ciuculete, Diana M.; Boström, Adrian E.; Tuunainen, Anna-Kaisa; Sohrabi, Farah; Kular, Lara; Jagodic, Maja; Voisin, Sarah; Mwinyi, Jessica; Schiöth, Helgi B.
Abstract: Generalized anxiety disorder (GAD) is highly prevalent among adolescents. An early detection of individuals at risk may prevent later psychiatric condition. Genome-wide studies investigating single nucleotide polymorphisms (SNPs) concluded that a focus on epigenetic mechanisms, which mediate the impact of environmental factors, could more efficiently help the understanding of GAD pathogenesis. We investigated the relationship between epigenetic shifts in blood and the risk to develop GAD, evaluated by the Development and Well-Being Assessment (DAWBA) score, in 221 otherwise healthy adolescents. Our analysis focused specifically on methylation sites showing high inter-individual variation but low tissue-specific variation, in order to infer a potential correlation between results obtained in blood and brain. Two statistical methods were applied, 1) a linear model with limma and 2) a likelihood test followed by Bonferroni correction. Methylation findings were validated in a cohort of 160 adults applying logistic models against the outcome variable "anxiety treatment obtained in the past" and studied in a third cohort with regards to associated expression changes measured in monocytes. One CpG site showed 1% increased methylation in adolescents at high risk of GAD (cg16333992, padj. = 0.028, estimate = 3.22), as confirmed in the second cohort (p = 0.031, estimate = 1.32). The identified and validated CpG site is located within the STK32B promoter region and its methylation level was positively associated with gene expression. Gene ontology analysis revealed that STK32B is involved in stress response and defense response. Our results provide evidence that shifts in DNA methylation are associated with a modulated risk profile for GAD in adolescence.